Process development for maximum carotenoids extraction from pumpkin (Cucurbita moschata) and its improvement through biogenesis manipulation - Norshazila Shahidan
Pumpkin is a vegetable loaded with carotenoid compounds that can support healthy living due to its antioxidant properties. Pumpkin is abundantly planted in Malaysia, with estimation of productions from 3559 to 8058 metric tonnes per year. However, the research on its carotenoid compound has not received the attention it deserves, from researchers or the government. This research was conducted to optimise carotenoid extraction and improve the individual carotenoid yield through biogenesis manipulation using different parts of pumpkin plants as well as pumpkin calluses. The primarily objective of this research was to optimise carotenoid extraction from pumpkin flesh. Results showed that the maximum yield of total carotenoid, predicted by design expert software 6.0 was 174.85 mg/l00g and would be obtained with the extraction duration of 4.45 hours, the temperature at 44.430C and solid-solvent ratio at 1:50. The second objective of the research was to isolate a-carotene, /3carotene and lutein from pumpkin flesh using open column chromatography technique, using two different adsorbents; Silica Gel and a combination of Magnesium Oxide:Hyflosupercel (1: 1;w/w). By comparing the two adsorbents used, the combination of Magnesium Oxide:Hyphlosupercel (1: 1; w/w) adsorbent provide a better separation and better stability for carotenoid compound within the 40 days of storage time. The third objective of the research was to study the carotenoid profiles of pumpkin flesh from different localities, storage and seasons. In terms of locality, the research investigated carotenoid content in pumpkin from Kelantan, Terengganu, Perak, Kedah and Melaka and it was analysed with HPLC analysis. Results showed that the individual carotenoid detected were a-carotene; which ranged from 1.26 mg/l00g to 10.20 mg/100g, ~-carotene; 29.16 mg/l00g to 154.76 mg/100g and small amounts of -lutein were also detected; which ranged from 0.22 mg/l00g to 0.46 mg/l00g. Lutein compound was not detected in pumpkin from Perak. In terms of storage and seasons, results showed that long term storage of pumpkin resulted in the accumulation of lutein and ~carotene, with a slight decrease in zeaxanthin. The amount of ~-carotene increased from 174.58 + 2.11 mg/100g to 692.87 + 22.02 mg/100g; lutein rose from 19.84 + 9.69 mg/100g to 59.48 + 1.65 mg/100g and zeaxanthin decreased from 2.71 + 0.12 mg/l00g to no amounts detected. Pumpkin that was collected three times a year had zeaxanthin compound only in the first season, while the amounts of ~-carotene and lutein compounds were highest in the second and third seasons. The fourth objective of the research was to find the optimum media for pumpkin callus initiation and to improve the-yield of individual carotenoid in pumpkin plants (leaves and stems) and pumpkin calluses through biogenesis manipulation. Results showed that under controlled conditions in the laboratory, the yield of individual carotenoid could be improved by involving an in vitro study using pumpkin plants and calluses with plant elicitor treatment under light and dark conditions. The plant elicitors used in this study were Ultra Violet light exposure, Polyethylene Glycol 4000, Jasmonic Acid, Salicylic Acid, Murashige and Skoog Salt. It was found that exposure to Ultra Violet light could improve the individual carotenoid (lutein) in pumpkin leaves and the yield of this compound was the highest among the other treatments (exclude control treatment). For the pumpkin stem, Salicylic Acid treatment under light condition was found to improve the same compound (lutein) to ten times higher than the controlled treatment. The major carotenoid in the pumpkin calluses Wcarotene), produced the highest yield at half strength treatment under light condition. Even though the carotenoid compound in pumpkin plants and calluses could be improved with the treatments mentioned above, the mechanisms involved regarding the treatment effects on carotenoid biosynthesis has not been well studied. Thus, further study should be conducted to understand the mechanisms better.